EFEKTIVITAS PELAKSANAAN PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA - Sari, Cica Nopika; Heriyanto, Meyzi; Rusli, Zaili (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Effectiveness Program Implementation of Community Empowerment-Based Community Empowerment. This study aims to describe the effectiveness of the implementation of PMBRW in Meranti Village, Rumbai District, Pekanbaru City. This study uses a qualitative descriptive research method approach. Primary data was obtained directly through interviews from key informants, namely the Village Head, the Facilitator Team leader, the RW Companion, the Chairperson of the RT / RW Forum. Secondary data is obtained from research documents. The results showed that the implementation of the PMBRW program started from the preparation stage, planning stages and implementation stages and viewed from the criteria in terms of achieving goals, integration and adaptation, that the community empowerment program in Meranti Village was considered effective.